2019
DOI: 10.1186/s12891-019-2568-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying musculoskeletal conditions in electronic medical records: a prevalence and validation study using the Deliver Primary Healthcare Information (DELPHI) database

Abstract: Background Musculoskeletal (MSK) conditions are a common presentation in primary care. This study sought to determine the prevalence of MSK conditions in primary care in Ontario and to validate the extent to which health administrative date billing codes accurately represent MSK diagnoses. Methods De-identified electronic medical records (EMR) from the DELPHI database in southwestern Ontario, which contains 2493 patients (55.6% female, mean age 50.3 years (SD = 22.2)) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…The legacy of ICD development disproportionately affects primary healthcare settings, where many encounters are symptom-based or undifferentiated and where preventive activities are common. Previous research has shown that neither do ICD-9 codes consistently capture the main problems addressed during a primary care encounter nor do they reflect the true complexity of a primary care visit ( Katz et al 2012 ; Ryan et al 2019 ). This becomes a problem when physician claims databases are used to describe complex patients, assess family physician workloads or inform the reorganization of primary care (e.g., alternative remuneration models, value-based care, Patient's Medical Home models).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The legacy of ICD development disproportionately affects primary healthcare settings, where many encounters are symptom-based or undifferentiated and where preventive activities are common. Previous research has shown that neither do ICD-9 codes consistently capture the main problems addressed during a primary care encounter nor do they reflect the true complexity of a primary care visit ( Katz et al 2012 ; Ryan et al 2019 ). This becomes a problem when physician claims databases are used to describe complex patients, assess family physician workloads or inform the reorganization of primary care (e.g., alternative remuneration models, value-based care, Patient's Medical Home models).…”
Section: Overviewmentioning
confidence: 99%
“…This becomes problematic when physicians record details about patient visits in their EMR: open text, rather than a code, is often used to capture relevant information and observations, which is more difficult to search for or utilize for secondary uses. Furthermore, the development of advanced features within EMRs, such as predictive or automated coding, is not possible with ICD-9, given that many encounters, conditions and symptoms do not have a corresponding ICD-9 code that accurately reflects the primary care visit ( Bhise et al 2018 ; Katz et al 2012 ; Ryan et al 2019 ). Another limitation is that ICD-9 is not extensible, which means that new conditions (e.g., COVID-19) cannot be easily added; most of its disease categories are considered full.…”
Section: Overviewmentioning
confidence: 99%
“…General practice databases have been used to determine the prevalence of some musculoskeletal complaints including arthritis, chronic back pain, gout, osteoporosis, spondyloarthropathies and rheumatoid arthritis in various countries [ 13 17 ]. Trends and trajectories of opioid prescription for people with general musculoskeletal conditions, [ 18 , 19 ] use of osteoporosis medicines in people with osteoporosis [ 16 ] and use of biologic drugs in people with psoriatic arthritis and ankylosing spondylitis [ 20 ] have also been examined.…”
Section: Introductionmentioning
confidence: 99%
“…General practice databases have been used to determine the prevalence of some musculoskeletal complaints including arthritis, chronic back pain, gout, osteoporosis, spondyloarthropathies and rheumatoid arthritis in various countries. [13][14][15][16][17] Trends and trajectories of opioid prescription for people with general musculoskeletal conditions, 18 19 use of osteoporosis medicines in people with osteoporosis 16 and use of biologic drugs in people with psoriatic arthritis and ankylosing spondylitis 20 have also been examined. However, to date the characteristics of patients presenting to general practice with musculoskeletal complaints and the healthcare utilisation at the primary care level has not been comprehensively examined using primary care databases.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used internationally to examine patterns of care for various conditions including respiratory tract infection, 6 cardiovascular disease, 7 chronic hepatitis C, 8 chronic kidney disease, 9 and diabetes [10][11][12] .General practice databases have been used to determine the prevalence of some musculoskeletal complaints including arthritis, chronic back pain, gout, osteoporosis, spondyloarthropathies and rheumatoid arthritis in various countries. [13][14][15][16][17] Trends and trajectories of opioid prescription for people with general musculoskeletal conditions, 18 19 use of osteoporosis medicines in people with osteoporosis 16 and use of biologic drugs in people with psoriatic arthritis and ankylosing spondylitis 20 have also been examined. However, to date the characteristics of patients presenting to general practice with musculoskeletal complaints and the healthcare utilisation at the primary care level has not been comprehensively examined using primary care databases.This study forms part of a larger project that is using data from the POpulation Level Analysis and Reporting (POLAR) dataset from 2014 to 2018 inclusive to examine patterns of care provided by GPs for people with musculoskeletal complaints.…”
mentioning
confidence: 99%